Penggunaan Google Form Pada Presensi dan Evaluasi Harian Kegiatan Pelatihan Kepemimpinan Administrator di BPSDM Provinsi Bengkulu Tahun 2022 - Irfan Setiawan; Alya Ramadanni; Ahmad Dhani Ramadhan; Naufal Diyarza Dwi (Jurnal Teknologi dan Komunikasi Pemerintahan, 2022)
Abstract Technological advances provide many benefits to people's lives, including government administration. In the field of government apparatus development activities, online presence can make it easy for activity organizers to record the attendance of participants. Different results when done manually. This study aims to find out how to use the Google Form application to record participant attendance at training activities at the Human Resources Development Agency in Bengkulu Province, and what are the obstacles in using Google Form in filling attendance in apparatus leadership activities and solutions to these obstacles. The research method used is a qualitative research method with a descriptive approach. Data collection by means of observation, interviews, and documentation on participants and organizers of training activities. The results of the study describe that the application of attendance through the Google form can help participants and organizers of leadership training in Bengkulu Province. In using presence through the Google form, several obstacles were found, such as some training participants who did not understand how to fill out an application, there were also several activity committees who did not have a Google account, and maintenance problems and an unstable network. Keywords : Administrator Leadership Training, Google Form, Attendance Attendance, Daily Activity Evaluation Abstrak Kemajuan teknologi banyak memberikan manfaat bagi kehidupan masyarakat termasuk juga pada penyelenggaraan pemerintahan. Dalam bidang kegiatan pengembangan aparatur pemerintahan, presensi online dapat memberikan kemudahan bagi para penyelenggara kegiatan untuk mendata kehadiran para peserta. Hal yang berbeda hasilnya bila dilakukan secara manual. Penelitian ini bertujuan untuk mengetahui bagaimana penggunaan aplikasi Google Form untuk mendata kehadiran peserta pada kegiatan Pelatihan di Badan Pengambangan Sumber Daya Manusia di Provinsi Bengkulu, dan bagaimana kendala dalam penggunaan Google Form dalam pengisian presensi dalam kegiatan kepemimpinan Aparatur serta soslusi atas kendala tersebut. Metode Penelitian yang digunakan adalah metode penelitian kualitatif dengan pendekatan deskriptif. Pengumpulan data dengan cara observasi, wawancara, dan dokumentasi pada peserta dan penyelenggara kegiatan pelatihan. Hasil penelitian menguraikan bahwa penerapan presensi melalui google form dapat membantu peserta dan penyelenggara pelatihan kepemimpinan di Provinsi Bengkulu. Pada penggunaan presensi melalui google form ditemukan beberapa kendala seperti beberapa peserta pelatihan yang belum mengerti cara mengisi aplikasi, terdapar juga beberapa panitia kegiatan yang belum memiliki akun Google, dan kendala maintenance serta terdapat jaringan yang kurang stabil. Kata kunci: Aplikasi Google Form, Pelatihan Kepemimpinan, Evaluasi Kegiatan Harian.